PENGEMBANGAN BISNIS DOC LAUNDRY BATAM - Maswita Giawa; Ganda Sirait (LPPM Universitas Putera Batam, 2024)
This research aims to examine the business development of laundry services in Batam, focusing on Doc Laundry. The main issue identified is to enhance operational efficiency and marketing through SWOT analysis. The research methods include literature review, qualitative and quantitative data collection, and SWOT analysis to identify business strengths, weaknesses, opportunities, and threats. Findings indicate potential for increased use of social media and digital payment as opportunities, alongside threats from competitors employing similar marketing strategies. Business development recommendations based on SWOT analysis are proposed to enhance competitiveness and efficiency in the laundry business in Batam. This study is expected to contribute to the development of SMEs in the laundry service sector.